Dance movement therapy for neurodegenerative diseases: A systematic review - Wu, Cheng-Cheng; Xiong, Huan-Yu; Zheng, Jie-Jiao; Wang, Xue-Qiang (Frontiers in Aging Neuroscience, 2022)
Background The proportion of the world's elderly population continues to rise, and the treatment and improvement of neurodegenerative diseases have become issue of public health importance as people live longer and many countries have aging populations. This systematic review aims to discuss the effects of dance movement therapy (DMT) on motor function, cognitive deficit, mood, and quality of life in people with neurodegenerative diseases, such as Parkinson's disease (PD), mild cognitive impairment (MCI), Alzheimer's disease (AD). Methods Two reviewers independently conducted systematic search on the Cochrane library, PubMed database, Web of Science Core Collection database, and Physiotherapy Evidence database until February 1, 2022. Only systematic analyses and randomized controlled trials were included and further analyzed. Results Thirty-three studies on PD, 16 studies on MCI, 4 studies on AD were obtained. This systematic review found that DMT substantially improved the global cognitive function, memory, and executive function on the population with MCI. Compared with the non-dance group, DMT remarkably improved general disease condition, balance, and gait for individuals with PD. The evidence of the efficacy of DMT on AD is insufficient, and further research is needed. Conclusion DMT can effectively improve the motor function and cognitive deficits in neurodegenerative diseases. Positive effects of DMT on the mood and quality of life in ND patients are controversial and require further evidence. Future research on the effects of DMT on AD requires scientific design, large sample size, long-term comprehensive intervention, and clear reporting standards. Systematic review registration www.osf.io/wktez, identifier: 10.17605/OSF.IO/UYBKT.